Current research in phytolith analysis : applications in archaeology and paleoecology - Pearsall, Deborah M.; Piperno, Dolores R. (MASCA research papers in science and archaeology ;, 1993)
Paleobotanical studies are assuming an increasingly important role in archaeology, providing information on prehistoric social structures, environments, and economic concerns. This volume presents the latest applications of phytolith analysis in archaeology and paleoecology. It demonstrates the versatility of the discipline.